Analisis Solusi dan Kontribusi terhadap Pemecahan Masalah di Lingkungan Sekolah - Mira Rahyuni; Sakilah; Nurhasnawati; Febrianti; Muhammad Rabbani Anugrah (Mataram University, 2026)
Problems in the school environment are one of the challenges in education that can affect the quality of the learning process and the achievement of educational goals. These problems are not only related to academic aspects, but also include learning motivation, student discipline, behavior, and social interaction in the school environment. Low learning motivation and less optimal learning processes are some of the problems that are still often found in educational activities.This study aims to examine the contributions of various parties in helping to solve problems that occur in schools. The method used is library research by collecting and analyzing various sources such as educational books, scientific journals, and literature related to learning, character education, and classroom management.The results of the study show that problems in schools are influenced by internal and external factors, such as family, school, community environment, and technological developments. Teachers act as guides and motivators, students as active subjects in learning, parents as supporters of education at home, and schools and communities as supporters in creating a conducive learning environment. Therefore, cooperation among all elements of education is very necessary to improve the quality of education as a whole.